Reducing progression of knee OA features assessed by MRI in overweight and obese women: secondary outcomes of a preventive RCT. Issue 6 (June 2016) - Landsmeer, M.L.A.; Runhaar, J.; van der Plas, P.; van Middelkoop, M.; Vroegindeweij, D.; Koes, B.; Bindels, P.J.E.; Oei, E.H.G.; Bierma-Zeinstra, S.M.A.
Summary: Objective: To evaluate the preventive effects of a randomized controlled trial on progression of Magnetic Resonance Imaging (MRI) features of knee osteoarthritis (OA) in overweight and obese women. Design: In a 2 × 2 factorial design, 2.5 years effects of a diet and exercise program and of glucosamine sulphate (double-blind, placebo-controlled) were evaluated in 407 middle-aged women with body mass index (BMI) ≥ 27 kg/m 2 without clinical signs of knee OA at baseline (ISRCTN 42823086). MRIs were scored with the MRI Osteoarthritis Knee Score (MOAKS). Progression was defined for bone marrow lesions (BMLs), cartilage defects, osteophytes, meniscal abnormalities and meniscal extrusion. Analyses on knee level were performed over the four intervention groups using adjusted Generalized Estimating Equations (GEE). Results: 687 knees of 347 women with mean age 55.7 years (±3.2 SD) and mean BMI 32.3 kg/m 2 (±4.2 SD) were analyzed. Baseline prevalence was 64% for BMLs, 70% for cartilage defects, 24% for osteophytes, 66% for meniscal abnormalities and 52% for meniscal extrusions. The diet and exercise program + placebo intervention showed significantly less progression of meniscal extrusion compared to placebo only (12% vs 22%, OR 0.50, 95% CI [0.27–0.92]). The interventions did not result in significant differences on other OA MRI features. Conclusions: In subjects at high risk for future knee OA development, a diet and exercise program, glucosamine sulphate and their combination showed small and mainly non-significant effects on the progression of OA MRI features. Only progression of meniscal extrusion was significantly diminished by the diet and exercise program.